Understanding Nutritional Disorders - A Comprehensive Analysis of Ayurvedic Concepts (International Journal of Ayurveda and Pharma Research, 2023)
Nutrition is a vital component of health at individual and community levels. Food system has changed dramatically after green revolution, but malnutrition still persists as a challenge. Coexistence of nutritional deficiency along with overweight and obesity is the double burden faced by most of the countries. Ayurveda explains nutrition, giving utmost importance to the state of individual, in a much customised manner. Conventionally the meaning of ‘Santarpana’ is understood as superfluity and ‘Apatarpana’ as deficiency. There are some inadequacies in this understanding. While examining the descriptions in Ayurvedic classics and comparing them with contemporary knowledge it is seen that Santarpana can lead to some deficiencies also. This understanding is very much important in present scenario. Nutritional disorder is not a single entity as far as Ayurveda is considered. It is spreading throughout a wide range of diseases, since Ahara is an essential component in the development of many diseases. Various kinds of nutritional deficiencies occur due to the impairment in Ahara parinamakara bhava, Ashtahara vidhi viseshayatana and Ahara vidhi vidhana. The primary and secondary causes of nutritional deficiency in modern science are mainly related to food and body respectively. But, for bringing out a better classification, this should be revised by including tertiary causes consisting of psychological factors and feeding habits.